Is the death penalty dying? : European and American perspectives - Sarat, Austin; Martschukat, Jürgen. (Cambridge [U.K.] ; New York, N.Y. : Cambridge University Press, 2011)
"Is the Death Penalty Dying? provides a careful analysis of the historical and political conditions that shaped death penalty practice on both sides of the Atlantic from the end of World War II to the twenty-first century. This book examines and assesses what the United States can learn from the European experience with capital punishment, especially the trajectory of abolition in different European nations. As a comparative sociology and history of the present, the book seeks to illuminate the way death penalty systems and their dissolution work, by means of eleven chapters written by an interdisciplinary group of authors from the United States and Europe. This work will help readers see how close the United States is to ending capital punishment and some of the cultural and institutional barriers that stand in the way of abolition"--Provided by publisher
Introduction : Transatlantic perspectives on capital punishment : national identity, the death penalty, and the prospects for abolition / Austin Sarat and Jürgen Martschukat -- The green, green grass of home : capital punishment and the penal system from a long-term perspective / Pieter Spierenburg -- Did anyone die here? : legal personalities, the supermax, and the politics of abolition / Colin Dayan -- Capital punishment as homeowners insurance : the rise of the homeowner citizen and the fate of ultimate sanctions in both Europe and the United States / Jonathan Simon -- The witnessing of judgment : between error, mercy, and vindictiveness / Evi Girling -- Unframing the death penalty : transatlantic discourse on the possibility of abolition and the execution of Saddam Hussein / Kathryn A. Heard -- Executions and the debate about abolition in France and in the United States / Simon Grivet -- Civilized rebels : death-penalty abolition in Europe as cause, mark of distinction, and political strategy / Andrew Hammel -- The death of dignity / Timothy V. Kaufman-Osborn -- Sovereignty and the unnecessary penalty of death : European and United States perspectives / Jon Yorke -- European policy on the death penalty / Agata Fijalkowski -- The long shadow of the death penalty : mass incarceration, capital punishment, and penal policy in the United States / Marie Gottschalk.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Capital punishment -- Europe; Capital punishment -- United States; Capital punishment -- History; Peine de mort -- Europe; Peine de mort -- États-Unis.; Peine de mort -- Histoire; SOCIAL SCIENCE -- Penology; Capital punishment; Europe; United States; Electronic book; dissertations; History; Academic theses; Thèses et écrits académiques.